THE INFLUENCE OF RISK MANAGEMENT ON PROJECT PERFORMANCE - PEGULESCU, Irina Andreea (Management & marketing (Craiova, Romania), 2023)
Through the project, an idea is implemented, based on several interconnected steps. The project is composed of several elements, without it cannot exist, mandatory elements that complete the project, by means of a well-developed project management. Thus, a link is created, positive or negative, between the elements of the project, which are interdependent and cannot exist one without the other. The present research is part of a broad analysis of the elements of project management, however, for the present research only two elements of the project were considered, namely risk management and performance, in order to discover the relationship created between them, the influences and effects on a project. It will also aim to outline some solutions to maintain, strengthen or improve, if necessary, the relationship between the elements of the project subject to the current research: risk management and project performance.